2006
DOI: 10.4049/jimmunol.177.9.6440
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Cortactin Coordinates Intercellular Adhesion Molecule-1 Clustering and Actin Cytoskeleton Remodeling during Polymorphonuclear Leukocyte Adhesion and Transmigration

Abstract: Endothelial cell ICAM-1 interacts with leukocyte ␤ 2 integrins to mediate adhesion and transmit outside-in signals that facilitate leukocyte transmigration. ICAM-1 redistribution and clustering appear necessary for leukocyte transmigration, but the mechanisms controlling ICAM-1 redistribution and clustering have not been identified. We recently reported that Src kinase phosphorylation of endothelial cortactin regulates polymorphonuclear cell (PMN) transmigration. In this study, we tested the hypotheses that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
95
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 38 publications
(59 reference statements)
13
95
0
Order By: Relevance
“…It was also shown that cortactin phosphorylation is required for leukocyte-mediated cytoskeletal remodeling as well as clustering of ICAM-1 (43). During, TEM, ICAM-1 clustering is required for numerous signaling processes in EC, thus Src-cortactin signaling may be the initiating event upstream of other ICAM-1-dependent signals (43). In line with this, expression of VE-cadherin Y658F or Y731F mutants had no effect on the distribution or recruitment of ICAM-1 to sites of leukocyte adhesion (data not shown) strengthening the idea that the ICAM-Src-cortactin pathway functions upstream of VE-cadherin phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also shown that cortactin phosphorylation is required for leukocyte-mediated cytoskeletal remodeling as well as clustering of ICAM-1 (43). During, TEM, ICAM-1 clustering is required for numerous signaling processes in EC, thus Src-cortactin signaling may be the initiating event upstream of other ICAM-1-dependent signals (43). In line with this, expression of VE-cadherin Y658F or Y731F mutants had no effect on the distribution or recruitment of ICAM-1 to sites of leukocyte adhesion (data not shown) strengthening the idea that the ICAM-Src-cortactin pathway functions upstream of VE-cadherin phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (22,43) have demonstrated a requirement for Src-mediated phosphorylation of cortactin specifically in paracellular leukocyte TEM. It was also shown that cortactin phosphorylation is required for leukocyte-mediated cytoskeletal remodeling as well as clustering of ICAM-1 (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of PECAM-1 recycling, leukocyte transmigration is arrested [10]. Cortactin-mediated rearrangement of the actin cytoskeleton [7] and intermediate filaments [11] is also critical for successful transmigration. Overall, these results reveal that endothelial cells are active participants in transmigration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the junctional protein vascular endothelial cadherin (VE-cadherin) is phosphorylated and redistributes during neutrophil transmigration [7][8][9]. This results in the formation of transient gaps that allow for the passage of neutrophils [9].…”
Section: Introductionmentioning
confidence: 99%